2004
DOI: 10.1194/jlr.r400010-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

PPAR- and LXR-dependent pathways controlling lipid metabolism and the development of atherosclerosis

Abstract: On June 1, 1889, 72 year old Charles-Edouard BrownSequard reported to the Societe de Biologie of Paris that he had injected himself with aqueous extracts of guinea pig and dog testes and within a short period of time experienced a remarkable enhancement in physical strength, intellectual capacity, and sexual potency (1). Brown-Sequard's self-experimentation was based on the then novel hypothesis that the testes were the source of a substance that was released into the circulation and exerted masculinizing effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
182
1
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(195 citation statements)
references
References 152 publications
6
182
1
6
Order By: Relevance
“…Indeed, ChIP-QPCR analysis of rosiglitazone-treated adipocytes at the seven sites did not reveal substantial PPAR␥ enrichment over IgG (data not shown). These findings indicate that there is little or no additional binding of PPAR␥ upon exogenous ligand stimulation, which is consistent with reported in vitro data indicating that DNA binding by PPAR␥ is ligand-independent (Li and Glass 2004;Lehrke and Lazar 2005).…”
Section: Identification and Validation Of Novel Ppar␥-binding Sitessupporting
confidence: 81%
“…Indeed, ChIP-QPCR analysis of rosiglitazone-treated adipocytes at the seven sites did not reveal substantial PPAR␥ enrichment over IgG (data not shown). These findings indicate that there is little or no additional binding of PPAR␥ upon exogenous ligand stimulation, which is consistent with reported in vitro data indicating that DNA binding by PPAR␥ is ligand-independent (Li and Glass 2004;Lehrke and Lazar 2005).…”
Section: Identification and Validation Of Novel Ppar␥-binding Sitessupporting
confidence: 81%
“…As a result, we found a consensus glucocorticoid receptor (GR) binding element in this region (Fig. 4b), instead of a classical PPAR-responsive element [15][16][17]. It is significant that the human ADIPOR1 promoter did not contain such a GR element in the corresponding region.…”
Section: Regulation Of Adipor2 Promoter By Rosiglitazonementioning
confidence: 86%
“…The peroxisome proliferator-activated receptors (PPARs) belong to a subfamily of nuclear receptors composed of three isoforms, PPARG, PPARA and PPARD [15][16][17]. PPARs are nutrient sensors that regulate the homeostasis of metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPT-1 mRNA expression in the soleus muscle and liver was not altered by HBA exposure in db/+m mice. The mRNA expressions of the transcription factors PPARα and PGC-1α were examined since the former was reported to control lipid metabolism (21,22) and the latter was reported to increase β-oxidation in brown adipocytes (23) or in skeletal muscle with enhanced mitochondria function coordinated with exercise (24), even though PGC-1α usually has roles in glucose metabolism to attribute a gluconeogenesis and mitochondria biosynthesis (25). Moreover, it has been shown that PGC-1α can cooperate with PPARα to express the genes of mitochondrial fatty acid oxidation enzymes such as CPT-1 in a hepatoma cell line (26).…”
Section: Resultsmentioning
confidence: 99%